Hubungan Kecerdasan Spiritual Terhadap Hasil Belajar Dasar Teknik Elektronika Di SMKN 1 Cikande - Alifah, Nur; Cahyono, Bagus Dwi; Desmira, Desmira (Jurnal Pendidikan, Sains Dan Teknologi, 2025)
This research is included in a quantitative research that aims to determine the relationship between intelligence and the learning outcomes of Basic Electronic Engineering (DTE) majoring in Electronic Engineering (TE) at SMKN 1 Cikande. The type of research used is correlation with data collection methods including questionnaires, observations and learning outcome tests. The stages in the study consist of 3 stages. The first stage of testing questionnaire items and learning outcome tests involved 3 experts, the second stage was a trial conducted on grade X students majoring in Electronics Engineering (TE) at SMKN 4 Kota Serang and the third stage of direct research of 36 respondents in grade X students majoring in Electronics Engineering (TE) at SMKN 1 Cikande. The data analysis technique used is descriptive analysis. The conditional analysis test consists of a normality test and a linearity test. Then the hypothesis test carried out consisted of a simple regression analysis. Based on the results of the study, it was shown that there was a relationship between spiritual intelligence and learning outcomes with a significance value of 0 < 0.05 and a relationship level of 32%.